Acceptability of RPG Simulators for Foreign Language Training in Japanese Higher Education. (February 2016) - Franciosi, Stephan J.
Background Role-playing game (RPG)/simulators for language and cultural training present an innovative foreign language (FL) instructional approach used in military and governmental contexts in the United States. Currently, developers of such RPGs may be seeking to expand into civilian applications for FL instruction, but the acceptance in potentially worthwhile markets such as Japanese higher education is uncertain. Purpose The purpose of this acceptability study was to better understand the possible interest in Japan by exploring the perceptions of RPG/simulators among FL faculty in Japanese higher education. Method The present study was grounded in Everett Rogers' theory of the Diffusion of Innovation and applied mixed methods to examine the perceived attributes of relative advantage, compatibility, and complexity that FL faculty hold with regard to the new technology. Results The results indicate that many FL faculty members perceive a beneficial impact on learner motivation, but are also unconvinced that such systems produce real outcomes. Educators also believe that RPG simulators would require an excessive amount of time to implement unless they are used as supplemental material. Finally, FL faculty members with a research interest in Computer-Assisted Language Learning (CALL) are more likely to have positive perspectives of RPG/simulators' relative advantage and compatibility than instructors with other research interests.